Respostas
respondido por:
3
Pode ser esclarecida por meio da formula: (sorvete...)
S = S0 + V.t + a.t²/2
Sendo:
Posição inicial: S0
Velocidade: V
Aceleração: a
S0 = 65 m
V = 2 m/s
a/2 = -3
a = -6 m/s²
Posição inicial: 65 m
Velocidade: 2 m/s
Aceleração: -6 m/s²
S = S0 + V.t + a.t²/2
Sendo:
Posição inicial: S0
Velocidade: V
Aceleração: a
S0 = 65 m
V = 2 m/s
a/2 = -3
a = -6 m/s²
Posição inicial: 65 m
Velocidade: 2 m/s
Aceleração: -6 m/s²
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás